Genomic insights and biotechnological potential of “Mesobacillus aurantius” strain S13: a canthaxanthin pigment-producing bacterium - Karthik, Shankar; Raman, Gurusamy; Srinivasan, Arumugam; Dastager, Syed Gulam; Wagh, Vasudev; Ayyadurai, Niraikulam (Gene Reports, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">This study explores the discovery and characterization of pigments, from a microorganism thriving under environmentally challenging conditions. Utilizing a polyphasic taxonomic approach, we successfully isolated and identified a bacterial strain S13 within the <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> genus and Bacillaceae family, designated as “<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus aurantius<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">” S13. We confirmed the species based on comprehensive phenotypic, physiological, and biochemical analyses, molecular phylogenetics, DNA–DNA hybridization, average nucleotide identity, and whole-genome sequencing. The strain S13 (MTCC13141 = VKM B-3583 = NBIMCC 9084) possesses a 4.81 Mbp genome that encodes genes for pigment production. Notably, this study uses various spectroscopic methods to characterize canthaxanthin, an orange pigment and delineates its biosynthetic pathway from the genome of S13. The methylerythritol phosphate (MEP) pathway and canthaxanthin biosynthesis genes highlight the capacity of the bacterium to synthesize crucial isoprenoids and terpenoids, including canthaxanthin. This research provides a detailed account of the isolation, characterization, and taxonomic classification of “<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus aurantius<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">” S13 and underscores the potential biotechnological applications of the bacterium in producing pharmaceuticals, biofuels, and cosmetics. Therefore, “<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Mesobacillus aurantius<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">” S13 is a potentially valuable microbial resource for the industrial production of isoprenoids and pigments.